From general toxicology to DNA disruption: A safety assessment of Plinia cauliflora (Mart.) Kausel. (10th August 2020) - Palozi, Rhanany Alan Calloi; Lorençone, Bethânia Rosa; Guarnier, Lucas Pires; Romão, Paulo Vitor Moreira; Marques, Aline Aparecida Macedo; Hulsmeyer, Ana Paula Cestari Rodrigues; Lourenço, Emerson Luiz Botelho; Tolouei, Sara Emilia Lima; da Silva, Gabriela Neubert; Curi, Tatiana Zauer; Passoni, Marcella Tapias; Dalsenter, Paulo Roberto; et al.
Abstract: Ethnopharmacological relevance: Plinia cauliflora (Mart.) Kausel (Myrtaceae) is popularly known as "jaboticaba" or "jaboticaba". The fruit is appreciated for both fresh consumption and the manufacture of jelly, juice, ice cream, fermented beverages, and liqueurs. The more widespread traditional use of the plant involves the treatment of diarrhea, which utilizes all parts of the plant, including the fruit peels. Aim of the study : We sought to elucidate possible risks of the administration of an ethanol-soluble fraction that was obtained from an infusion of P. cauliflora fruit peels (SEIPC). We performed a series of experiments to evaluate possible toxicity, in which we administered SEIPC orally both acutely and repeatedly for 28 days. We also evaluated possible endocrine-disruptive and genotoxic effects in eukaryotic cells. The possible mutagenic activity of SEIPC was evaluated using reverse mutation (Ames) assays. Materials and methods: SEIPC was produced and chemically characterized by LC-DAD-MS. Acute toxicity and behavioral and physiological alterations were evaluated in the modified Irwin test. Respiratory rate, arterial blood gas, electrocardiography, respiratory rate, heart rate, and blood pressure were evaluated, and hematological, biochemical, and histopathological analyses were performed after 28 days of oral treatment. The comet assay, mammalian erythrocyte micronucleus test, uterotrophic test, Hershberger bioassay, and AMES test were performed using appropriate protocols. Results: From SEIPC, ellagic acid and derivatives, flavonols and anthocyanidins, as well as citric acid and gallic acid, were annotated by LC-DAD-MS. We did not observed any significant toxic effects after acute or prolonged SEIPC treatment. No endocrine-disruptive or mutagenic effects were observed. Conclusions: The present study found that SEIPC did not cause any significant alterations of various corporeal systems, including cardiac electrical activity, body temperature, respiratory rate, and arterial pressure. No alterations of biochemical, hematological, or blood gas parameters were observed. SEIPC did not cause any perturbations of the endocrine system or mutagenic, cytotoxic, or genotoxic effects. These findings substantiate the safe clinical use of P. cauliflora . Graphical abstract: Image 1 Highlights: Plinia cauliflora (Mart.) Kausel (Myrtaceae) is popularly known as "jaboticaba". The main traditional use of fruit peels involves the treatment of diarrhea. We assessment the acute toxicity and after prolonged treatment. Its mutagenic, genotoxic and endocrine-disrupting potential was also assessed. These findings substantiate the safe clinical use of P. cauliflora .